Pijat Bayi untuk Meningkatkan Nafsu Makan di Desa Dadapayam - Asraria Arsfandi; Isfaizah; Maria Karmelia Wung Song; Ivana Sika Yon; Elita Niasirgia Rahayu (Universitas Ngudi Waluyo, 2022)
Infants are children aged 0 to 12 months. Every baby goes through a stage of growth and development in his lifetime (Rusli, 2013). Growth and development is a continuous, continuous process and growth is part of the development process (Wong, 2016). Baby Massage is a touch therapy in direct contact with the body that can provide a sense of security and comfort for babies. Infant massage is a direct contact touch therapy with the body that can provide a sense of security and comfort for toddlers. A mother's touch and hugs are basic needs of a toddler. If massage is done regularly, it will increase catecholamine hormones (epinephrine and norepinephrine) which can trigger growth and development stimulation because it can increase appetite, increase body weight, and stimulate the development of brain structure and function (ashi.2018). Infants aged 4 -10 months who have decreased appetite and lack of mother's knowledge about infant massage to increase appetite. Based on this, community service will be carried out with the topic of